Certain Issues Concerning the Romanian Regulation of the Good Faith Principle in Civil and Civil Procedural Matters (Journal of Legal Studies, 2016)
One way for individuals and legal entities to pursue legitimate rights and/or interests is the judicial path. The civil proceedings as a form of settling civil litigations is governed by different principles. Among these stands out the principle of good faith, which involved the exercise in good faith of rights in both civil and procedural matters, the exercise in good faith of procedural rights, a principle which has gained new meanings after the entry into force of the new Code of Civil Procedure, as well as the new Civil Code.